Composição química dos extratos de Miconia ibaguensis (MELASTOMATACEAE) e avaliação do potencial biológico - Sehnem, Gabriela Sella (2024)
Miconia ibaguensis, a member of the Melastomataceae family, is found in the Cerrado biome. Species of the genus Miconia are recognized for their medicinal properties, which motivated the unpublished chemical and biological study of the species M. ibaguensis. Thus, this work aims to explore the chemical composition and potential medicinal properties of M. ibaguensis. The hexane (EH) and ethanolic (EE) extracts were obtained by maceration, and dichloromethane (FD), ethyl acetate (EAE), n-butanol (FB), and aqueous (AF) fractions were obtained by liquid-liquid extraction from EE. Antimicrobial activities revealed that FAE presented relevant antifungal activity against Candida spp., with minimum inhibitory concentration (MIC) between 1.95 and 3.90 μg mL–1, standing out against Candida glabrata. FAE and FB exhibited antibacterial activity, with MIC between 25 and 50 μg mL–1 for Streptococcus sanguinis and Fusobacterium nucleatum. FAE demonstrated high antioxidant activity in the 2,2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH), ferric reducing antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC) methods, with 94.85% inhibition and IC50 of 1.74 μg mL–1, in the DPPH method; 654.01 μmol Etrolox/gsample in the FRAP method and 3,698.88 μmol Etrolox/gsample in the ORAC method. Regarding the antidiabetic assays, EE obtained the best result in inhibiting the α-amylase enzyme with 91.22% inhibition and IC50 of 8.42 μg L–1. In the glycoxidation analysis, FAE showed the best inhibition (86.66%) in the bovine serum albumin (BSA)-fructose method. However, no extract showed significant results for the inhibition of α-glucosidase. In the study of the chemical composition by HPLC-(–)-IES-MS/MS, metabolites of the classes of flavonoids, hydrolyzable tannins, triterpenoids, and phenolic acids were noted in EE and the fractions, suggesting that the antimicrobial potential observed in M. ibaguensis must be associated with these compounds. This study enriches our understanding of the biodiversity present in the Cerrado, the chemosystematics of the genus Miconia, and the pharmacological potential of M. ibaguensis.